Da māmūrīno da jarāyimo aw da ʻāmo gaṭo aw amnīyat pah khilāf da jarāyimo jazā uṣūlnāmah : pah khilāf da jarāyimo jazā uṣūlnāmah (Dawlatī Ma̤tbaʻah, 1973)
Regulations for Afghan government officials regarding crimes, corruption.